Design of Process Products Based on Image Processing Multimode Interaction - Wei Sun (Hindawi Limited, 2021)
With the development of modern science and technology and more and more image processing systems, related technologies are becoming more and more complex. The application of image processing technology can be seen in various fields of society, such as medical field, aerospace field and life, and entertainment field. Due to the increasing amount of information on the picture, the requirements for the speed and clarity of image processing are also increasing. The existence of various external factors will lead to the production of image products and objects between the error and distortion problems. In order to make the process product design more authentic and reliable, this paper studies the process product design based on image processing multimode interaction. It uses radiometric correction and geometric correction to process distorted images and uses GPU parallel computing technology to accelerate the correction process. In this paper, this technology is applied to the visual recognition of welding robot, and the experiment shows that the product produced by the image processed by this module can obviously reduce the error.